Developmental validation of a custom panel including 165 Y-SNPs for Chinese Y-chromosomal haplogroups dissection using the ion S5 XL system. (January 2019) - Wang, Mengge; Wang, Zheng; He, Guanglin; Liu, Jing; Wang, Shouyu; Qian, Xiaoqing; Lang, Min; Li, Jienan; Xie, Mingkun; Li, Chengtao; Hou, Yiping
Highlights: A customized panel including 165 Y-SNPs for paternal lineage classifications and forensic pedigree searches was designed. A high-resolution haplogroup tree defining 160 different haplogroups aiming at Chinese populations was constructed. The customized 165 Y-SNPs MPS panel could be applied to case-type samples and the sample with high degradation index. Abstract: Massively parallel sequencing (MPS) technology has the capability to genotype hundreds to thousands of SNPs from multiple samples, with high coverage in a single experimental run. MPS, which enables high-resolution Y haplogrouping from limited DNA resources, has attracted much interest in Y-chromosomal applications, particularly human forensics and anthropological studies. Previously, we selected and designed a 72 Y-SNPs MPS panel aiming at the Chinese population for providing the basic structure of the haplogroup tree, and then additional Y-SNPs were screened out for further subdivision into different populations by using pyrosequencing technology. In the present study, we designed a customized MPS panel that includes 165 Y-SNPs based on our previous studies and evaluated the sequencing performance, sensitivity and the ability of the MPS-SNP panel to analyze case-type samples using the Ion S5 XL System. In the concordant study, only four Y-SNPs presented missing genotypes due to low coverage reads, and five SNPs were prone to being designated heterozygotes, whereas the designation of the other SNPs were fully consistent with the results obtained from other Y-SNP typing tools. The analyst-interpreted Y-SNP profiles demonstrated that the targeted Y-SNPs, except for the nine poorly performing Y-SNPs, performed well and could acquire achievable high-resolution. Moreover, this MPS panel could be adapted to case-type samples, and single source complete profiles could be stably obtained using 1 ng of input DNA. In summary, this MPS Y-SNP panel offers a straightforward sample-to-haplogroup workflow that would be beneficial for paternal lineage classification and forensic pedigree searches, and the present results provide support for the application of MPS technology in SNP analysis.